What’s New in Addiction Prevention in Young People: A Literature Review of the Last Years of Research - Kempf, Cédric; Llorca, Pierre-Michel; Pizon, Frank; Brousse, Georges; Flaudias, Valentin (Frontiers in Psychology, 2017)
Rationale. Addiction prevention is a major public health problem, particularly concerning young people. Despite the consensus that primary prevention is essential, the evaluation of its impact is questioned. Objective. The objective of this paper is to assess the latest knowledge of addiction prevention programs for young people. Method. Review a collection of research articles using a keyword-based search on three databases: Pubmed, Eric and PsycInfo. The research was carried out using three groups of keywords and the eligibility study was completed using two criteria: articles published between 2010 and 2017, and articles in refereed journals. Results. Of a total of 13,720 articles in the three databases, 32 studies were included in the review and listed in a grid with five themes: authors, type of population, total population, addictive behavior and results. Four categories were created based on the objective of the studies: the evaluation of prevention strategies, the study of risk factors for consumption, the prevalence study and other subjects studied. The analysis of the corpus was used to establish a list of risk factors to be taken into consideration in future interventions and research. A list of key elements for performing effective interventions and future research is also proposed. Conclusion. The understanding of the prevention strategies implementation process is discussed as a central element for future research, which will combine stakeholders and researchers. The complexity of the situations and the multifactorial aspects of addiction prevention in young people require a multidisciplinary approach involving the various stakeholders and researchers.